Butylated Hydroxytoluene (BHT) Inhibits PIN1 Exocytosis From BFA Compartments in Arabidopsis Roots - Paponov, Ivan A.; Budnyk, Vadym; Paponov, Martina; Teale, William; Palme, Klaus (Frontiers in Plant Science, 2020)
The activity of polarly localized PIN-FORMED (PIN) auxin efflux carriers contributes to the formation of auxin gradients which guide plant growth, development, and tropic responses. Both the localization and abundance of PIN proteins in the plasma membrane depend on the regulation of PIN trafficking through endocytosis and exocytosis and are influenced by many external and internal stimuli, such as reactive oxygen species, auxin transport inhibitors, flavonoids, plant hormones, and other signals. Here, we investigated the regulation of endosomal PIN cycling by using a Brefeldin A (BFA) assay to study the effect of a phenolic antioxidant ionol, butylated hydroxytoluene (BHT), on the endocytosis and exocytosis of PIN1 and PIN2. BHT is one of the most widely used antioxidants in the food and feed industries, and as such is commonly released into the environment; however, the effect of BHT on plants remains poorly characterized. Preincubation of Arabidopsis seedlings with BHT before BFA treatment strongly enhanced the internalization of PIN1 into BFA compartments. After the simultaneous application of BHT and NAA, the NAA effect dominated PIN internalization suggesting the BHT effect occurred downstream to that of NAA. Washing seedlings with BHT after BFA treatment prevented the release of PIN1 from BFA compartments back to the plasma membrane, indicating that BHT application inhibited PIN1 exocytosis. Overall rates of PIN2 internalization were less pronounced than those of PIN1 in seedlings pre-incubated with BHT before BFA treatment, and PIN2 exocytosis was not inhibited by BHT, indicating a specific activity of BHT on PIN1 exocytosis. Comparison of BHT activity with other potential stimuli of PIN1 and PIN2 trafficking (e.g., H2O2 [ROS], salt stress, reduced glutathione [GSH], dithiothreitol [DTT], and flavonoids) showed that BHT has a new activity distinct from the activities of other regulators of PIN trafficking. The findings support BHT as a potentially interesting pharmacological tool for dissecting PIN trafficking and auxin transport.